(untitled) (Research, Society and Development, 2020)
The objective was to evaluate the variation of salt content in sun-dried meat and its impacts on shelf life and consumer preference. For this purpose, beef steaks of the hard topside type (Biceps femoris) were cut and then salted with 2.5, 5, 7.5 and 10% sodium chloride. Microbiological and physical-chemical analyses were performed on days 0, 24hrs after salting, and again after 3,6,9,12 and 14 days of refrigerated storage, in addition to the sensory profile. It was observed that the increased sodium chloride content in meat provided greater microbiological stability during the storage period. However, the characteristics of water retention capacity, weight loss by cooking and shear strength of the meat varied negatively, with the increase in salt content, showing greater weight loss after cooking and lower water retention capacity, resulting in a meat with a harder texture, greater loss of juiciness and softness. Regarding the sensory analysis, the different salt contents did not interfere in the visual quality attributes analyzed, however, the 2.5% salt level showed good acceptance and purchase intention, being the salt concentration the ideal to guarantee qualitative attributes and food safety for the elaboration of sun-dried meat.